2020
DOI: 10.1108/ssmt-02-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 96.5Sn–3Ag–0.5Cu/fullerene composite solder under isothermal ageing and high-current stressing

Abstract: Purpose The purpose of this paper is to investigate the effect of fullerene (FNS) reinforcements on the microstructure and mechanical properties of 96.5Sn3Ag0.5Cu (SAC305) lead-free solder joints under isothermal ageing and electrical-migration (EM) stressing. Design/methodology/approach In this paper, SAC305 solder alloy doped with 0.1 Wt.% FNS was prepared via the powder metallurgy method. A sandwich-like sample and a U-shaped sample were designed and prepared to conduct an isothermal ageing test and an EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Kumar et al [85,86] confirmed that the addition of CNTs could refine the microstructure of SAC solder. The other carbon-based nanomaterials of FNSs was also added into SAC305 solder [41,43]. They confirmed that the grain size of β-Sn displays an evident reduction trend with the addition of FNSs.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Kumar et al [85,86] confirmed that the addition of CNTs could refine the microstructure of SAC solder. The other carbon-based nanomaterials of FNSs was also added into SAC305 solder [41,43]. They confirmed that the grain size of β-Sn displays an evident reduction trend with the addition of FNSs.…”
mentioning
confidence: 68%
“…Consequently, trace amount of alloying elements (Ni [8][9][10], Mn [11], Bi [12], Co [13,14], Cr [15], Al [9], Sb [10], Fe [16], and rare earth (RE) [17,18]) is incorporated with Sn-based lead-free solder to enhance the comprehensive properties. Moreover, with the popularity and utilization of nanometer materials fabricating technology, the nanometer particles are doped with Sn-based lead-free solder to improve the comprehensive properties, such as nanometer oxide (Al 2 O 3 [19][20][21], BaTiO 3 [22], Y 2 O 3 [23], TiO 2 [24][25][26][27], and ZrO 2 [28,29]), nanometer carbide ( [30,31]), nanometer IMC (Cu 6 Sn 5 [32][33][34]), and carbon-based nanometer materials (carbon nanotubes (CNTs) [35][36][37], graphene [38][39][40], and fullerenes [41][42][43]). Generally speaking, the addition of nanoparticles acts as reinforcing phase in the Sn-based lead-free composite solder alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Fullerene (FNS) nanomaterial exhibits excellent electrical properties. Incorporating fullerene FNS in the study resulted in a reduction in the average thickness of the Cu 6 Sn 5 (IMC) layer at the initial composite solder joint interface compared to conventional solder joints [ 113 ]. The FNS particles in the solder joint can act as barriers to inhibit the diffusion and migration of Sn and Cu atoms [ 114 ].…”
Section: Methods and Measures Of Electromigration Mitigation For Snbi...mentioning
confidence: 99%
“…Alloying or particle-strengthening methods can address these shortcomings [7]. In particular, doped nanomaterials have attracted significant interest in developing high-performance tin-based, lead-free solders [8][9][10].…”
Section: Introductionmentioning
confidence: 99%